Catalytic Enantioselective Synthesis of Halocyclopropanes. Issue 18 (16th March 2016) - Pons, Amandine; Ivashkin, Pavel; Poisson, Thomas; Charette, André B.; Pannecoucke, Xavier; Jubault, Philippe
Abstract: A catalytic asymmetric synthesis of halocyclopropanes is described. The developed method is based on a carbenoid cyclopropanation of 2‐haloalkenes with tert ‐butyl α‐cyano‐α‐diazoacetate using a chiral rhodium catalyst that permits access to a broad range of highly functionalized chiral halocyclopropanes (F, Cl, Br, and I) in good yields, moderate diastereoselectivity, and excellent enantiomeric ratios. The reported methodology represents the first general catalytic enantioselective approach to halocyclopropanes. Abstract : 3‐Membered rings : Catalytic asymmetric synthesis of halocyclopropanes is described. The developed method is based on a carbenoid cyclopropanation of 2‐haloalkenes with tert ‐butyl α‐cyano‐α‐diazoacetate using a chiral rhodium catalyst that permits access to a broad range of highly functionalized chiral halocyclopropanes (F, Cl, Br, and I) in good yields, moderate diastereoselectivity, and excellent enantiomeric ratios.